Medical ethics today : the BMAs handbook of ethics and law - English, Veronica; Sommerville, Ann.; Brannan, Sophie; British Medical Association (Chichester, West Sussex : Wiley-Blackwell, 2012)
This is your source for authoritative and comprehensive guidance from the British Medical Association (BMA) Medical Ethics Department covering both routine and highly contentious medico-legal issues faced by health care professionals. The new edition updates the information from both the legal and ethical perspectives and reflects developments surrounding The Mental Capacity Act, Human Tissue Act, and revision of the Human Fertilisation and Embryology Act.
The doctor-patient relationship -- Consent, choice, and refusal : adults with capacity -- Treating adults who lack capacity -- Children and young people -- Confidentiality -- Health records -- Contraception, abortion, and birth -- Assisted reproduction -- Genetics -- Caring for patients at the end of life -- Euthanasia and physician assisted suicide -- Responsibilities after a patient's death -- Prescribing and administering medication -- Research and innovative treatment -- Emergency situations -- Doctors with dual obligations -- Providing treatment and care in detention settings -- Education and training -- Teamwork, referral, delegation, and shared care -- Public health dimensions of medical practice -- Reducing risk, clinical error, and poor performance.
Includes bibliographical references and index.
Print version record.
Keywords: Medical ethics -- Great Britain -- Handbooks, manuals, etc; Ethics, Medical; Jurisprudence; MEDICAL -- Ethics; Medical ethics; Great Britain; Great Britain; Electronic books; Handbooks and manuals